Correction: Research on cultural and creative design method of 2022 World Cup lamps based on AHP-FCE. - Tao Wang; HongZhu Chen; Basyarah Hamat; YanXiao Zhao (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0286682.].